2005
DOI: 10.1381/0960892054222858
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial of Placement of the Laparoscopic Adjustable Gastric Band: Comparison of the Perigastric and Pars Flaccida Pathways

Abstract: The PF pathway is as effective as the PG pathway in generating substantial weight loss, improved health and improved quality of life and is significantly less likely to be associated with prolapse (slippage). It is recommended as the primary dissection pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(107 citation statements)
references
References 11 publications
4
103
0
Order By: Relevance
“…O'Brien et al [5] reported, in a prospective randomized study of 202 patients followed for 24 months, that the pars flaccida pathway makes a significant difference in gastric prolapse reduction. Similar improvement in SF36 scores for quality of life and weight loss were also recorded.…”
Section: Discussionmentioning
confidence: 99%
“…O'Brien et al [5] reported, in a prospective randomized study of 202 patients followed for 24 months, that the pars flaccida pathway makes a significant difference in gastric prolapse reduction. Similar improvement in SF36 scores for quality of life and weight loss were also recorded.…”
Section: Discussionmentioning
confidence: 99%
“…This variability is unlikely related to different gastric banding devices or techniques, as previous trials have demonstrated. 28,29 Our data not only demonstrate marginal absolute weight loss with LAGB, but also superior comparative weight loss with LSG and RYGB, and greater reduction in obesity-related comorbidities with RYGB. Accordingly, in a shared decision-making model, our study will inform patients and referring physicians of the relative lack of effectiveness of the band for weight loss and comorbidity resolution.…”
Section: Comparisonmentioning
confidence: 63%
“…There are two known techniques for dissection before LAGB placement: (1) The traditional perigastric pathway that requires dissection between the lesser curvature of stomach and lesser omentum, across the apex of the lesser sac, to the angle of His; and (2) the more recent technique of using the Pars flaccida pathway, in which dissection is made from the base of the right crus, along the left crus to the angle of His. O'Brien et al 12 found that the using the Pars flaccida pathway is as effective as using the perigastric pathway in generating substantial weight loss, improved health, and improved quality of life, and it is significantly less likely to be associated with prolapse (slippage). Although the presented data suggest as a general recommendation that surgeons should prefer the Pars flaccida approach, Di Lorenzo et al 13 suggested that the perigastric technique must be considered because in expert hands, it has good results as well, with a low complication rate.…”
Section: Discussionmentioning
confidence: 99%